Phyllodes tumor in an adolescent female - Baldiwala, Aafrin S.; Vaidya, Hiren P. (International Surgery Journal, 2021)
Phyllodes is a tumor of breast. This fibro-epithelial lesion occurs in less than 1% of all breast tumors in female. They can be benign, borderline or malignant. It commonly occurs in age group of 45-50 years. It is also known as cystosarcoma phyllodes/ serocystic disease of Brodie. Treatment can be either wide local excision or mastectomy to achieve histologically clear margin. Palpable axillary lymphadenopathy can be identified in up-to 10-15% of patients but less than 1% has pathological positive nodes. Mammography and ultrasonography are main imaging modalities. Here, we present a case of a 14-year-old female presenting with a rapidly enlarging breast mass, which was ultimately found to be a Phyllodes tumor.